(De)Humanization of the Chinese and the Malays in the Sin Chew Daily and the New Straits Times : a semiotic study of the 2013 Malaysian elections - Qian, Xiuxiu
As observed by many scholars, electoral politics in Malaysia is conducted along ethnic lines. With reference to the recent 2013 general elections, it witnessed a further erosion of racial relations between, especially, the Malays and the Chinese. Immediately after the polling results were released, it was so aghast, to the extent that national leaders openly described it as a “Chinese Tsunami” which, on the other hand, unexpectedly triggered a further round of fierce racial disputes. The exchange of words has been recorded integrally in the print media; the media were in the front line to raise issues, disseminate information, as well as to influence voters' decisions. Hence, the current study is designed to investigate the humanization and dehumanization features in the performance of actors from two notable ethnicities, the Chinese and the Malays by going through a semiotic analysis on their viewpoints and comments about each other in two mainstream print media in Malaysia: the New Straits Times and the Sin Chew Daily. The linguistic fragments were culled from both dailies published two weeks before and after the 13th Malaysia general elections (from 21 April to 19 May, 2013). As a result, four elements have been scrutinized and it is revealed that both actors employed enormous factuality and high identification signs, a small quantity of hedging devices, and a larger proportion of distrust performatives than trust performatives.